2013
DOI: 10.4028/www.scientific.net/amm.372.586
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of Open Circuit Voltage Fluctuation of Quantum Dot Based Solar Cell Using InN

Abstract: This paper reports the improvement of open circuit voltage stability of solar cell using InN based quantum dot in the active layer of the device structure. We have analyzed theoretically the temperature dependence of the open circuit voltage of the solar cell to investigate its fluctuation using Ge and InN based quantum dot in the active layer of the solar cell. Numerical results obtained are compared. The comparison results reveal that the open circuit voltage has been reduced a little bit but the fluctuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The rate of change of these characteristics has been analyzed theoretically in this present research work. Rosli et al (2013) reported that the open circuit voltage of solar cell is related to the bandgap energy of the active layer semiconductor material of the solar cell by the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…The rate of change of these characteristics has been analyzed theoretically in this present research work. Rosli et al (2013) reported that the open circuit voltage of solar cell is related to the bandgap energy of the active layer semiconductor material of the solar cell by the following equation:…”
Section: Methodsmentioning
confidence: 99%